2020
DOI: 10.1039/c9ra08676e
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a headspace needle-trap method for rapid quantitative estimation of butylated hydroxytoluene from cosmetics by hand-portable GC-MS

Abstract: Butylated hydroxytoluene (BHT) is widely used as a stable and inexpensive antioxidant in skin care products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The use of single-layer graphitic carbon nitride-modified graphene composite (C 3 N 4 @G), as well as β-cyclodextrin/graphene oxide-modified fibres were employed for the extraction of PAHs and fragrances, respectively [ 131 , 132 ]. In most cases, GC analysis was carried out after SPME [ 123 , 124 , 125 , 127 , 128 , 129 , 131 , 132 ], directly performing analytes’ desorption in the instrument injector—although LC analysis has also been employed [ 130 ]. In this last case, the desorption was performed, employing a small volume of organic solvent.…”
Section: Sample Preparation Strategies For Cosmetics Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The use of single-layer graphitic carbon nitride-modified graphene composite (C 3 N 4 @G), as well as β-cyclodextrin/graphene oxide-modified fibres were employed for the extraction of PAHs and fragrances, respectively [ 131 , 132 ]. In most cases, GC analysis was carried out after SPME [ 123 , 124 , 125 , 127 , 128 , 129 , 131 , 132 ], directly performing analytes’ desorption in the instrument injector—although LC analysis has also been employed [ 130 ]. In this last case, the desorption was performed, employing a small volume of organic solvent.…”
Section: Sample Preparation Strategies For Cosmetics Analysismentioning
confidence: 99%
“…Finally, analytes were adsorbed on a polyacrylate (PA) fibre. The combination of a purge-trap with a headspace needle trap device (NTD) and portable GC-MS analysis has also recently been proposed to determine the antioxidant BHT in cosmetics [ 128 ], demonstrating the feasibility of utilizing a hand-portable GC-MS for the real-time estimation of this compound, facilitating quality control measurements by inspecting agencies.…”
Section: Sample Preparation Strategies For Cosmetics Analysismentioning
confidence: 99%
“…PCPs have been reported to contain a variety of industrial chemicals to increase the softness, flexibility, adhesiveness, longevity, and antiseptic and antibacterial efficiencies and prevent exposure to ultraviolet (UV) radiation and oxidation. Bisphenols, parabens, and UV filters in more than half of PCP samples, such as body washes, haircare, makeup, and skin lotions, were investigated in two U.S. studies. , Phthalate esters (PAEs) and organophosphate esters (OPEs) were detected in nail polish where they are mainly used as ingredients to hold color . Synthetic antioxidants [e.g., butylated hydroxytoluene (BHT)] are also added to PCPs to prevent oxidation …”
Section: Introductionmentioning
confidence: 99%
“…9 Synthetic antioxidants [e.g., butylated hydroxytoluene (BHT)] are also added to PCPs to prevent oxidation. 10 The frequent use of beauty products may increase human exposure to industrial chemicals through dermal contact, inhalation, and oral intake. 8,11,12 Many known chemicals added to beauty products have been recognized for their toxic effects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Repeated short-term exposure to BHT caused hepatic toxicity in male and female rats. Several studies have shown that BHT can induce tumors development in the liver of animals when BHT orally ingested [24]. Additionally, it caused the development of hepatocellular tumors in rats and mice, DNA damage in monkeys and endocrine disruption in Zebra fish [25].…”
Section: Introductionmentioning
confidence: 99%